The opinion of French pulmonologists and palliative care physicians on non-invasive ventilation during palliative sedation at end of life: a nationwide survey - V. Guastella; G. Piwko; A. Greil; C. Lambert; A. Lautrette (BMC Palliative Care, 2021)
Abstract Background Deciding to withdraw non-invasive ventilation (NIV) at end-of-life (EOL) in patients with chronic respiratory failure is a challenge. The European Association for Palliative Care recommends not maintaining artificial therapies that could prolong life during palliative sedation (PS) at EOL. The aim of this survey was to assess palliative care physicians’ and pulmonologists’ opinion on withdrawing or maintaining NIV in patients with chronic respiratory failure during PS at EOL. Methods From April to May 2019, we performed a prospective survey among pulmonologists (n = 1545) and palliative care physicians (n = 631) in France to determine the prevalence of opinion in favour of maintaining NIV and identify the factors associated with opinion in favour of withdrawing or maintaining NIV with multiple logistic regression. Results A total of 457 participants were enrolled comprising 202 pulmonologists and 255 palliative care physicians. An opinion in favour of maintaining NIV was found in 88 (19.3 95%CI [15.7; 23.2]) physicians comprising 57 (28.2%) pulmonologists and 31 (12.2%) palliative care physicians (p < 0.001). The factors associated with an opinion in favour of maintaining NIV were spending time looking for advanced directives (AD) in the patient’s file (odds ratio (OR): 6.54, 95%CI [2.00; 21.32], p = 0.002) and personal ethics of physicians (OR: 17.97, 95%CI [9.52; 33.89], p < 0.001). The factor associated with an opinion in favour of withdrawing NIV was palliative care training (OR: 0.31, 95%CI [0.16; 0.60], p < 0.001). The three main reasons in favour of maintaining NIV among the nine identified were emotional comfort for close relatives, reducing discomfort of dyspneoa and anticipation of suffocation. Conclusion In France, around 20% of pulmonologists and palliative care physicians declared an opinion in favour of maintaining NIV during PS at EOL because of their personal ethics and spending time looking for AD, if any, in the patient’s file. Palliative care training can stimulate reflection help foster a change of opinion about practices, especially in the case of patients with NIV during PS at EOL.